Poverty in The Qur'an: A Thematic Study of Verses on Poverty Through a Cultural-Structural Approach - Zulfan Nabrisah; Ahmad Fajar Shodik; Imamuddin Imamuddin (Islamika Inside: Jurnal Keislaman dan Humaniora, 2025)
Poverty has been a persistent problem since ancient times. In Indonesia, poverty rates continue to fluctuate. According to the Central Bureau of Statistics, the number of impoverished individuals as of March 2023 was 25.90 million out of a total population of 278.8 million. It is essential to continue examining why poverty persists globally today, especially since Islam has provided extensive guidance on this issue within the Qur’an. Motivated by these facts, the author has explored poverty from the Qur’anic perspective using Abd al Hayy al Farmawi's thematic interpretation method, analyzed with sociology through cultural and structural approaches. Culturally, several causes of poverty have been identified: first, laziness and lack of perseverance; second, consumptive, inefficient, and stingy behaviors; third, individual destruction; and fourth, a lack of knowledge and education. Structurally, the causes include neoliberalism, capitalism, monopolies, social discrimination, and the arrogance of power. Qur’anically prescribed countermeasures culturally include genuine endeavor, a lifestyle of frugality, efficiency, wisdom, individual reconstruction, and education. Structurally, government intervention is required. The proposed solutions include the prohibition of monopolies, the establishment of justice, and pro-poor policies.